2001
DOI: 10.1046/j.1365-2664.2001.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of weeds by spring wheat Triticumaestivum increases with crop density and spatial uniformity

Abstract: Summary1. Recent advances in our understanding of the advantage of initial size in competition among individual plants (size-asymmetric competition) suggest that the potential for many crops to suppress weeds is much greater than generally appreciated. We hypothesize that this potential can be realized if: (i) the crop density is increased significantly and (ii) the crop is regularly (uniformly) distributed in two-dimensional space rather than sown in traditional rows. 2. We tested these hypotheses by sowing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
243
3
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(273 citation statements)
references
References 29 publications
18
243
3
9
Order By: Relevance
“…Seeding rate has been shown to be a useful cultural control to reduce weed competition in conventionally grown crops. Increased seeding rate can reduce weed biomass and weed seed production (Wilson et al 1995;Weiner et al 2001;Korres and Froud-Williams 2004). At higher densities, wheat is expected to be at a competitive advantage by more effectively competing with weeds for resources (Mohler 1996).…”
mentioning
confidence: 99%
“…Seeding rate has been shown to be a useful cultural control to reduce weed competition in conventionally grown crops. Increased seeding rate can reduce weed biomass and weed seed production (Wilson et al 1995;Weiner et al 2001;Korres and Froud-Williams 2004). At higher densities, wheat is expected to be at a competitive advantage by more effectively competing with weeds for resources (Mohler 1996).…”
mentioning
confidence: 99%
“…In a study by Kaur et al (2002) have shown that even seed distribution increases crop establishment and per unit area and thus resulting in higher competitiveness against weeds. In another experiment, significant effects of both crop density and spatial distribution on weed growth were observed (Weiner et al 2001). They further reported that high crop density and grid sowing pattern recorded 60% less weed biomass and produced 60% higher yield as compared to lower crop densities and normal sowing in rows.…”
Section: Introductionmentioning
confidence: 82%
“…This modification can improve plants' water usage due to lower interspecific competition and consequently greater water supply during critical periods. It also allows greater solar radiation penetration inside the canopy, increased air flow and also improves pesticide application quality, especially fungicides (Weiner et al 2001).…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%